Conservative, surgical, and percutaneous treatment for mitral regurgitation shortly after acute myocardial infarction. (31st August 2021) - Haberman, Dan; Estévez-Loureiro, Rodrigo; Benito-Gonzalez, Tomas; Denti, Paolo; Arzamendi, Dabit; Adamo, Marianna; Freixa, Xavier; Nombela-Franco, Luis; Villablanca, Pedro; Krivoshei, Lian; Fam, Neil; Spargias, Konstantinos; et al.
Abstract: Aims : Severe mitral regurgitation (MR) following acute myocardial infarction (MI) is associated with high mortality rates and has inconclusive recommendations in clinical guidelines. We aimed to report the international experience of patients with secondary MR following acute MI and compare the outcomes of those treated conservatively, surgically, and percutaneously. Methods and results : Retrospective international registry of consecutive patients with at least moderate-to-severe MR following MI treated in 21 centres in North America, Europe, and the Middle East. The registry included patients treated conservatively and those having surgical mitral valve repair or replacement (SMVR) or percutaneous mitral valve repair (PMVR) using edge-to-edge repair. The primary endpoint was in-hospital mortality. A total of 471 patients were included (43% female, age 73 ± 11 years): 205 underwent interventions, of whom 106 were SMVR and 99 PMVR. Patients who underwent mitral valve intervention were in a worse clinical state (Killip class ≥3 in 60% vs. 43%, P < 0.01), but yet had lower in-hospital and 1-year mortality compared with those treated conservatively [11% vs. 27%, P < 0.01 and 16% vs. 35%, P < 0.01; adjusted hazard ratio (HR) 0.28, 95% confidence interval (CI) 0.18–0.46, P < 0.01]. Surgical mitral valve repair or replacement was performed earlier than PMVR [median of 12 days from MI date (interquartile range 5–19) vs. 19 days (10–40), P < 0.01]. The immediate procedural success did not differ between SMVR and PMVR (92% vs. 93%, P = 0.53). However, in-hospital and 1-year mortality rates were significantly higher in SMVR than in PMVR (16% vs. 6%, P = 0.03 and 31% vs. 17%, P = 0.04; adjusted HR 3.75, 95% CI 1.55–9.07, P < 0.01). Conclusions : Early intervention may mitigate the poor prognosis associated with conservative therapy in patients with post-MI MR. Percutaneous mitral valve repair can serve as an alternative for surgery in reducing MR for high-risk patients. Graphical Abstract: